2017
DOI: 10.1093/mnras/stx1937
|View full text |Cite
|
Sign up to set email alerts
|

Neutron star dynamics under time-dependent external torques

Abstract: The two component model describes neutron star dynamics incorporating the response of the superfluid interior. Conventional solutions and applications involve constant external torques, as appropriate for radio pulsars on dynamical timescales. We present the general solution of two component dynamics under arbitrary time dependent external torques, with internal torques that are linear in the rotation rates, or with the extremely non-linear internal torques due to vortex creep. The two-component model incorpor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Spin-up rate of NS: The spin-up torque (N ) measured from the simulated results of Paper I was such that it corresponded to a spin-up rate of ∼ 5.0 × 10 −14 Hz s −1 . The value agrees well with observational results and predictions from other models (Bildsten 1998;Revnivtsev & Mereghetti, 2015;Sanna et al 2017;Bhattacharyya & Chakrabarty, 2017;Gügercinoǧlu & Alpar, 2017;Ertan 2018).…”
Section: Introductionsupporting
confidence: 90%
“…Spin-up rate of NS: The spin-up torque (N ) measured from the simulated results of Paper I was such that it corresponded to a spin-up rate of ∼ 5.0 × 10 −14 Hz s −1 . The value agrees well with observational results and predictions from other models (Bildsten 1998;Revnivtsev & Mereghetti, 2015;Sanna et al 2017;Bhattacharyya & Chakrabarty, 2017;Gügercinoǧlu & Alpar, 2017;Ertan 2018).…”
Section: Introductionsupporting
confidence: 90%
“…In this paper by analysing the glitches displaying exponential relaxation it is shown that glitch phenomenon can be used to deduce valuable information about neutron star internal structure, in particular on the interior magnetic field configuration. To this end, a model incorporating glitch induced offset ∆Ωc and vortex line-flux tube creep process in the outer core of the neutron star is considered and its 1 Gügercinoglu & Alpar (2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of uniform rotation, the quantities 𝐼 s , Ω s , 𝐼 c , and Ω c represent body-averaged approximations to the realistic behavior (Sidery et al 2010;Haskell et al 2012); see also Antonelli & Pizzochero (2017) for an axially symmetric generalization. Moreover the superfluid is pinned to nuclear lattice sites (Link & Epstein 1991;Avogadro et al 2008;Seveso et al 2016) and quantized magnetic fluxoids (Bhattacharya & Srinivasan 1991;Ruderman et al 1998;Sidery & Alpar 2009;Gügercinoǧlu & Alpar 2017;Drummond & Melatos 2017) in the inner crust, leading to non-linear stick-slip dynamics in Ω s which do not emerge explicitly from (2). Some aspects of the stick-slip dynamics are captured phenomenologically by hydrodynamic models (Haskell et al 2013;Khomenko & Haskell 2018), but others are not, e.g.…”
Section: Equations Of Motionmentioning
confidence: 99%
“…1 Evidence for the two-component model comes from theoretical nuclear physics [Yakovlev et al (1999); Chamel (2017); Lattimer & Prakash (2016) and references therein] and from the time-scale and quasiexponential form of rotational glitch recoveries [Alpar et al (1984a); van Eysden & Melatos (2010); Haskell & Melatos (2015) and references therein]. Historically the parameters of the two-component model have been estimated observationally in two independent ways: (i) by fitting timing models to individual glitch recoveries (Alpar et al 1986;Sidery et al 2010;van Eysden & Melatos 2010;Espinoza et al 2011;Chamel 2013;Howitt et al 2016;Graber et al 2018;Ashton et al 2019); and (ii) by studying long-term spin down, as affected by the relative inertia of the superfluid and crust, for example (Es-pinoza et al 2011;Andersson et al 2012;Chamel 2013;Barsukov et al 2014;Gügercinoǧlu & Alpar 2017).…”
Section: Introductionmentioning
confidence: 99%